2017
DOI: 10.1530/erc-16-0505
|View full text |Cite
|
Sign up to set email alerts
|

The clinical importance of quantifying body fat distribution during androgen deprivation therapy for prostate cancer

Abstract: Androgen deprivation therapy (ADT) is now considered a mainstay in the treatment of metastatic and locally advanced prostate cancer (PCa). Despite well-established benefits of ADT in relation to overall survival, this treatment has been associated with a number of adverse effects, particularly with regard to key cardiometabolic risk factors including the development of insulin resistance, dyslipidemia and increases in total and regional fat mass. In non-ADT populations, increased levels of visceral adipose tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 123 publications
(180 reference statements)
1
11
0
Order By: Relevance
“…Suggested causes include the onset of premature menopause during treatment, predisposing women toward weight gain . Our results suggest that female participants had lower abdominal obesity (measured by waist‐hip ratio), and higher body fat percentage (measured by DXA) compared with male participants, which is consistent with known sex differences in fat distribution between men and women , the older age of the men and the use of androgen‐deprivation therapy to treat prostate cancer .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Suggested causes include the onset of premature menopause during treatment, predisposing women toward weight gain . Our results suggest that female participants had lower abdominal obesity (measured by waist‐hip ratio), and higher body fat percentage (measured by DXA) compared with male participants, which is consistent with known sex differences in fat distribution between men and women , the older age of the men and the use of androgen‐deprivation therapy to treat prostate cancer .…”
Section: Discussionsupporting
confidence: 81%
“…The risk of developing obesity is increased in breast and prostate cancer patients compared to the general population, and may be exacerbated by the effects of cancer treatments . Indeed, several studies have reported weight gain as a common phenomenon among breast cancer patients and survivors .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…total, regional and intramuscular fat mass [216] . For instance, potential increases in subcutaneous and visceral fat may contribute to the marked increase in cardiometabolic disorders in men treated with ADT [20,56,217] .…”
Section: The Clinical Implications Of Androgen Deprivation Therapy-rementioning
confidence: 99%
“…However, the high cost of CT and MRI scan acquisition and data processing, complications with claustrophobic and severely obese individuals (body mass index [BMI] ≥ 40 kg/m 2 ), and in the case of CT, high exposure to ionising radiation [76,111] , may in part explain why these techniques are less commonly used in the research setting. Advancements in the precision and availability of dual-energy xray absorptiometry (DXA) [118,119] and peripheral quantitative CT (pQCT) [117] for quantifying regional fat mass and CSA have led to suggestions that these measures may have the potential to be of clinical importance with regard to risk stratification and clinical decision making in men treated with ADT [216] .…”
Section: Introductionmentioning
confidence: 99%